E2F1 Affects the Therapeutic Response to Neoadjuvant Therapy in Breast Cancer. (17th September 2022) - Ye, Xinxing; Zhou, Jie; Tong, Dandan; Wang, Dandan; Wang, Hui; Guo, Jixue; Kang, Xinmei
Abstract : This study is aimed at screening genes for predicting the sensitivity response and favorable outcome of neoadjuvant therapy in breast cancer. We downloaded neoadjuvant therapy genetic data of breast cancer and separated it into the pathological complete response (pCR) group and the non-pCR group. Differential expression analysis was performed to select the differentially expressed genes (DEGs). After that, we investigated the enriched biological processes and pathways of DEGs. Then, core up/down protein-protein interaction (PPI) network was, respectively, constructed to identify the hub genes. A transcription factor-target gene regulation network was built to screen core transcription factors (TFs). We found one upregulated DEG (KLHDC7B) and four downregulated DEGs (TFF1, LOC440335, SLC39A6, and MLPH) overlapped in three datasets. All DEGs were mainly enriched in pathways related to DNA biosynthesis, cell cycle, immune response, metabolism, and angiogenesis. The hub genes were KRT18, IL7R, HIST1H1A, and E2F1. The core TFs were HOXA9, SPDEF, FOXA1, E2F1, and PGR. RT-qPCR suggested that E2F1 was overexpressed in MCF-7, but HOXA9 was low-expressed. Western blot suggested that the MAPK signal pathway was inhibited in MCF-7/ADR. That is to say, some genes and core TFs can predict the sensitivity response of neoadjuvant therapy in breast cancer. And E2F1 may be involved in the process of drug resistance by regulating the MAPK signaling pathway. These might be useful as sensitive genes for the efficacy evaluation of neoadjuvant chemotherapy in breast cancer.